2015
DOI: 10.14740/wjon950e
|View full text |Cite
|
Sign up to set email alerts
|

Role of Topotecan in Non-Small Cell Lung Cancer: A Review of Literature

Abstract: Topotecan (TPT), a chemotherapeutic agent, is a topoisomerase-I inhibitor. Topoisomerase-I is a nuclear enzyme that relieves torsion strain in DNA by opening single strand breaks which helps in DNA replication. TPT inhibits this enzyme, thus preventing DNA replication and causes cell death. TPT has demonstrated to have broad spectrum of antitumor activity in tumors like cervical, ovarian, endometrial and small cell lung cancers (SCLCs). The intravenous (IV) formulation of the drug is currently approved by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…* indicates p < 0.05 comparing resistant cell line with or without Ko143 to parental cell line with or without Ko143; # indicates p < 0.05 comparing a group with Ko143 to the corresponding cell line group without Ko143. (Vennepureddy et al, 2015), but the development of MDR in tumors remains a serious obstacle for successful treatment. In MDR-exhibiting NSCLC cells that acquire resistance to one drug often develop resistance to a range of other structurally and functionally unrelated anticancer agents, resulting in cancer recurrence, and even relapse or death (Osmani et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…* indicates p < 0.05 comparing resistant cell line with or without Ko143 to parental cell line with or without Ko143; # indicates p < 0.05 comparing a group with Ko143 to the corresponding cell line group without Ko143. (Vennepureddy et al, 2015), but the development of MDR in tumors remains a serious obstacle for successful treatment. In MDR-exhibiting NSCLC cells that acquire resistance to one drug often develop resistance to a range of other structurally and functionally unrelated anticancer agents, resulting in cancer recurrence, and even relapse or death (Osmani et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy is the predominant form of treatment for advanced NSCLC. Topotecan is one of the first-line drugs in treating NSCLC with a favorable side effect profile ( Vennepureddy et al, 2015 ), but the development of MDR in tumors remains a serious obstacle for successful treatment. In MDR-exhibiting NSCLC cells that acquire resistance to one drug often develop resistance to a range of other structurally and functionally unrelated anticancer agents, resulting in cancer recurrence, and even relapse or death ( Osmani et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that TPT has a good prospect as a first-or second-line treatment for progressed or relapsed NSCLC because of its high efficacy and favorable side effect profile (Vennepureddy et al, 2015). However, as TPT is FIGURE 3 | Effect of cabozantinib combined with topotecan on the expression of ABCG2 and topoisomerase I (TOP1).…”
Section: Discussionmentioning
confidence: 99%
“…First, pemetrexed + cisplatin polychemotherapy started because this regimen combination was reported to be effective and well-tolerated in NSCLC patients with brain metastases (16). Then the patient was treated with topotecan, a Topoisomerase I inhibitor that previously showed encouraging results in the NSCLC treatment (17). Finally, the patient was prescribed with crizotinib.…”
Section: Discussionmentioning
confidence: 99%